Grandmaster of demonic cultivation = Mo dao zu shi. 2 - Moxiangtongxiu (Seven Seas Entertainment, 2022)
"Following the trail of a dismembered corpse, Wei Wuxian and Lan Wangji arrive at the gates of Yi City: an old, abandoned town shrouded in mist and restless spirits. A fiendish foe awaits them in the shadows, heralding a tale of heartbreak and tragedy. When the mysterious corpse's identity is finally revealed, the hunt for its killer plunges Wei Wuxian back into the depths of the cultivation world's politics, where he must keep his enemies close and Lan Wangji even closer."--Page 4 of cover.